Con ternura de hijo quiere el cubano bueno a Costa Rica - Reyes-Quiñones, Edelmis Cristina (2017)
For many years, Costa Rica was a host country for  Cubans forced to leave the land that saw them born, fleeing the Spanish yoke and the misery in which the country got plunged. This work aims to analyze on some loyal and good patriots who, from 1870 to 1898, came to live on Tico soil and on their feelings towards this nation; the ways  they integrated into Costa Rican society and were recognized in fields such as education, arts, letters, science, law.